IMPLEMENTASI DAN STRATEGI MEDIA SOSIAL PT LEADERSHIP NASIONAL ASIA UNTUK PROMOSI PELATIHAN SDM - Zalfa Alya Rifa; Hari Otang Sasmita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has encouraged companies to use social media as an effective promotional tool to reach consumers and strengthen brand image. PT Leadership Nasional Asia utilizes various social media platforms to promote its training programs and professional certifications. This study aims to describe the implementation of social media in supporting the promotion and marketing of human resource (HR) training programs, identify strategies for planning, producing, and distributing promotional content, and analyze challenges in its management. The study employs a qualitative descriptive method using interviews, participatory observation, and literature review as data collection techniques. Data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data presentation, and conclusion drawing. The findings indicate that social media, particularly Instagram, plays an important role in promoting training programs and strengthening the company’s image, despite challenges related to team coordination, content standardization, and audience engagement optimization.